Perceptions of Farming Community in Relation to Problems in Farming and Prospects of Coconut Mite Management in Bangladesh - Islam, M. Nazirul; Rahman, M. Sayedur; Islam, M. Ishaqul; Samsunnahar, M.; Karim, A. N. M. Rezaul; Azad, A. K. (International Coconut Community Journal, 2018)
A study was conducted to analyze community perception on homestead agro-biodiversity and conservation of coconut genetic resources at Bagharpara Upazila (Sub district) of Jashore district, Bangladesh in October 2011. Tools and techniques of Participatory Rural Appraisals (PRA) were utilized to identify the socio-economic factors and agronomic practices influencing homestead agro-biodiversity. The participants identified coconut as a leading species in the homesteads. Communities suspected that the wave (electro-magnetic) generating from mobile phone towers was the cause of damaging coconut in their villages. Being disheartened with continuous yield loss, the farmers have resorted to fell down their coconut trees and shifted to cultivating fruit trees or suitable field crops. The research team used the matrices of PRA to develop a problem tree, which marked mite infestation in coconut as the focal problem. The developed problem-tree was transposed into an objective tree. Based on the objective tree, the research team was able to develop and implement a three-year research project on mite management in coconut involving farmers as implementers. The intervention stimulated community knowledge and skills towards mite management and conservation of unique traditional coconut varieties.